What is Science? Defining Science by Numbers, 1920-2000 - Godin, Benoit (Foresight and STI Governance, 2009)
The quest for the definition of science took up scientific minds long ago. Different epochs and philosophical schools developed their own interpretations of the term which quite often were in the center of scientific debates. Nevertheless, the beginning of the 20th century gave rise to a new – official – definition which was to help state bodies in measuring and estimating the effect R&D activities had on the economy and society. The fact should be mentioned that this definition has never been systematically examined. Thus, this paper attempts to fill the gap. Its first part (published in the given issue) documents how research became the central concept for measuring and talking about science. It traces the history of official statistics on science over the 20th century, follows with looking at the concept of research through the categories or types of research like basic and applied research, and finally turns to definitions of research proper, centered on an institutionalized conception of science. Part II of the paper (see issue 3/2009) examines the controversies surrounding the official definition of science and the efforts undertaken to broaden it.